2015
DOI: 10.2527/jas.2014-7651
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of sows was improved by administration of a sporing bacillary probiotic (Bacillus subtilis C-3102)

Abstract: This field study assessed the efficacy of a probiotic based on viable spores of Bacillus subtilis C-3102 (Calsporin; Calpis Co. Ltd., Japan) on the health status and productivity of sows and their litters through 2 full, sequential reproductive cycles from service of the first cycle to weaning of the second cycle. Fifty-six sows were allocated to 2 experimental groups, an untreated control (T1) group and a probiotic-treated (T2) group that received the same basal feed as the T1 group plus the probiotic at an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 27 publications
3
60
3
Order By: Relevance
“…Oral administration of B. subtilis can exert a range of beneficial effects, including improvement of growth, enhancement of meat characteristics, optimizing the balance of intestinal microbiota, prevention and treatment of some diarrheal diseases, and reduction of serum cholesterol [9, 10]. For these reasons, B. subtilis has attracted considerable attention as a potentially beneficial dietary supplement for animal health.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of B. subtilis can exert a range of beneficial effects, including improvement of growth, enhancement of meat characteristics, optimizing the balance of intestinal microbiota, prevention and treatment of some diarrheal diseases, and reduction of serum cholesterol [9, 10]. For these reasons, B. subtilis has attracted considerable attention as a potentially beneficial dietary supplement for animal health.…”
Section: Introductionmentioning
confidence: 99%
“…P<0.05). Kritas et al (2015) did not observe any effect of 3×10 5 CFU of Bacillus subtilis C-3102/g of diet on neonatal mortality of piglets.…”
Section: Pre-weaning Productive Parametersmentioning
confidence: 60%
“…Previously, a probiotic compound containing B. licheniformis and B. subtilis spores was supplemented to sows for two reproductive cycles (Kritas et al., ). Kritas et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kritas et al. () showed that giving B. subtilis C‐3102 to sows helped them return to estrus more rapidly. In the present study, probiotic supplementation to PED‐infected sows significantly reduced the number of days to recurrence of estrus (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation